INfluenza Vaccine Indication During therapy with Immune checkpoint inhibitors: a transversal challenge. The INVIDIa study. (17th October 2018) - Bersanelli, Melissa; Giannarelli, Diana; Castrignanò, Paola; Fornarini, Giuseppe; Panni, Stefano; Mazzoni, Francesca; Tiseo, Marcello; Rossetti, Sabrina; Gambale, Elisabetta; Rossi, Ernesto; Papa, Anselmo; Cortellini, Alessio; et al.
Aim: Considering the unmet need for the counseling of cancer patients treated with immune checkpoint inhibitors (CKI) about influenza vaccination, an explorative study was planned to assess flu vaccine efficacy in this population.Methods: INVIDIa was a retrospective, multicenter study, enrolling consecutive advanced cancer outpatients receiving CKI during the influenza season 2016–2017.Results: Of 300 patients, 79 received flu vaccine. The incidence of influenza syndrome was 24.1% among vaccinated, versus 11.8% of controls; odds ratio: 2.4; 95% CI: 1.23–4.59; p = 0.009. The clinical ineffectiveness of vaccine was more pronounced among elderly: 37.8% among vaccinated patients, versus 6.1% of unvaccinated, odds ratio: 9.28; 95% CI: 2.77–31.14; p < 0.0001.Conclusion: Although influenza vaccine may be clinically ineffective in advanced cancer patients receiving CKI, it seems not to negatively impact the efficacy of anticancer therapy.